O setor de pedras preciosas e suas dinâmicas socioeconômicas - Soledade (1997-2006) - Palmeira, Gilmar Afonso de Matos (2009)
This research work aims a historical analysis of the social and economical importance of the sector fo precious stones for community of Soledade, as well its social, economical and environmental dynamics an problems in the period of time from 1997 to 2006. The research was performed with the use of books related to the objet of study, also considering business development and oral history based on that background it was possible to analyse the reasons why the sector of stones became the main economical activity of Soledade overtaking the historical possibilities of forming and wood and shoe industries. The research clarifies why the businessmen prefer to export rough stones rather than make jewels and stone crafts creating more direct and indirect jobs. It is analysed the environmental aspects and de worke´s health. One approaches the importance of associations, universities, private entities and syndicates involved in its development. It is made a brief report about in Soledade, checking their contribution for the municipal reserves and for the internal and external market system of the local economy